Análisis psicosocial de la violencia: entre el conflicto y el desarrollo social - Malvaceda Espinoza, Eli L. (2009)
Following recent events in our country, with the aim of improving the study and prevention of conflicts for a better economic and social development that contributes to the quality of life and mental health of individuals, this article begins by exploring the concepts of violence and aggression and outlines the conceptual distinction between them, also delves into issues such as intentionality and social value, basic budgets and components as the formal structure of the act, personal equation, the context enabler and the ideological background in the development of violence. Follows the path initiated in 1989 by Ignacio MartínBaró, adapting to the Peruvian case.